2009
DOI: 10.1088/1751-8113/43/1/015202
|View full text |Cite
|
Sign up to set email alerts
|

Periodic orbits for an infinite family of classical superintegrable systems

Abstract: We show that all bounded trajectories in the two dimensional classical system with the potential V (r, ϕ) = ω 2 r 2 + and does not depend on k. This agrees with our earlier conjecture suggesting that the quantum version of this system is superintegrable.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
131
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(137 citation statements)
references
References 13 publications
6
131
0
Order By: Relevance
“…This proves superintegrability and supports recent studies by Tremblay,Turbiner and Winternitz [1,8] of the potentials with k rational where it has been demonstrated that all the orbits are closed. We also studied a new class of systems (7) and showed that again the systems are superintegrable and demonstrated how to find a maximal set of constants polynomial in the momenta.…”
Section: Discussionsupporting
confidence: 90%
“…This proves superintegrability and supports recent studies by Tremblay,Turbiner and Winternitz [1,8] of the potentials with k rational where it has been demonstrated that all the orbits are closed. We also studied a new class of systems (7) and showed that again the systems are superintegrable and demonstrated how to find a maximal set of constants polynomial in the momenta.…”
Section: Discussionsupporting
confidence: 90%
“…As an instructive example, we apply this technique to construct the two-dimensional version of the quantum harmonic oscillator (19), focusing the analysis on its superintegrability properties. To this aim, let us apply the coproduct map to the Hamiltonian Ĥ :…”
Section: The Quantum Casementioning
confidence: 99%
“…As recently showed, the coalgebraic analysis can also be used to give new insights about the already known classifications of superintegrable systems: in [17] it has been shown that a canonical transformation can generate different coalgebraic systems which, once embedded in higher dimensional spaces, generate genuinely new superintegrable systems as deformations, or generalizations, of TTW systems [18,19] to non-Euclidean spaces. The same philosophy has been reproposed in [20], involving a gauge transformation applied to a two-dimensional scalar Hamiltonian.…”
Section: Introductionmentioning
confidence: 99%
“…Such an operator will coincide with the operator 4ωΓ, coming from the supersymmetric extension and given in (8), provided the coefficients of ab †…”
Section: Comparison Between Both Extensions Of H Kmentioning
confidence: 99%